Numerical validation of two-phase slug flow and its liquid holdup correlation in horizontal pipeline - Pao, W. (Trans Tech Publications Ltd, 2017)
The transition of one flow regime into another is a very common phenomena in pipeline networks, which can be potentially hazardous for the structural integrity of the pipeline. Literature review showed that there is almost no reported detail investigation of transitional flow whereby the fluid constituents change from one regime to another especially slug transition. Most of the open research papers focused on slug flow regime and its liquid holdup in horizontal pipelines and channels have been carried out on experimental test rigs. The objective of this study is to explore oil-gasoil vapour slug transition and its liquid holdup in a 3.15 inch diameter horizontal straight pipe. The abrupt change in gas/liquid velocities, which causes transition of flow patterns is analyzed using incompressible Volume of Fluid (VOF) method, along with Piecewise Linear Interface Construction (PLIC) technique to capture the sharp front of segregated gas-liquid interface. Slug liquid holdup derived from the present numerical model is compared to existing experimental correlations in the literature. © 2017 Trans Tech Publications, Switzerland.